Tracing the pathways to Yathrib (Al-Madinah): A GIS-based analysis of settlement patterns and ancient trade networks - Mohamed Metwaly; Abdullah Alshami (PLoS ONE, 2026)
Ancient human activities in the arid Arabia peninsula are considered one of interesting research subjects in the landscape archaeological field to understand the relationships between human occupation strategies, material culture, and the natural environment in the past. Focusing on Al-Madinah Region of the Arabian Peninsula, a landscape of profound historical and archaeological significance, the research integrates Multi-Criteria Spatial Analysis (MCSA) using Geographic Information Systems (GIS) and the Analytic Hierarchy Process (AHP) with Least-Cost Path (LCP) modeling. The study aimed to (i) evaluate environmental suitability for historical settlements and (ii) reconstruct optimal caravan routes converging on Yathrib (Al-Madinah). Six principal environmental and topographic variables were evaluated: lithology, elevation, slope, drainage density, distance to watercourses (wadis), and the soil classification. A balanced weighting system was implemented (Consistency Ratio = 0.01), where proximity to watercourses, slope, and soil were identified as the primary controlling factors. The resulting settlement suitability map identified 32.01% of the study area as highly suitable. For the reconstruction of caravan routes, a cost surface was generated based on four parameters: distance to watercourses, slope, elevation, and lithology to simulate LCPs to major archaeological sites, including Khaybar, Al-Hinakiyah, Dadan–AlUla–Hegra, and the coastal port of Al-Jar. Quantitative validation of these modeled routes against verified historical trade stations demonstrates that hydrological accessibility and terrain favorability jointly governed patterns of ancient human settlement and mobility, offering a replicable methodology for exploring trade networks and habitation dynamics in arid landscapes.